When a figure is reflected over one of the axis there is only a change on the sign of one of the coordinates.
When the reflection is done over the x-axis the transformation follows the rule
![(x,y)\rightarrow(x,-y)](https://img.qammunity.org/2023/formulas/mathematics/college/d7a29ae1nc5itoub5zbvfqbwxpczq9rzr6.png)
When the reflection is done over the y-axis the transformation follows the rule
![(x,y)\rightarrow(-x,y)](https://img.qammunity.org/2023/formulas/mathematics/college/ikcitr9ov18gnuy0131ezdtc936qt485rg.png)
According to this if we reflect triangle ABC over the x axis then
![\begin{gathered} A(2,10)\rightarrow A^(\prime)(2,-10) \\ B(3,-4)\rightarrow B^(\prime)(3,4) \\ C(-3,1)\rightarrow C^(\prime)(-3,-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/h7qy02v2ulvr2ykyrhe6do565x27wmz356.png)
If we reflect the triangle over the y axis
![\begin{gathered} A(2,10)\rightarrow A^(\prime)(-2,10) \\ B(3,-4)\rightarrow B^(\prime)(-3,-4) \\ C(-3,1)\rightarrow C^(\prime)(3,1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/p9df1znawbpi4x852dyvdkdiv497xuyt7z.png)